Capital in the twenty-first century - Piketty, thomas; Goldhammer, Arthur (Cambridge, Massachusett Belknap Press of Harvard University Press, 2014)
What are the grand dynamics that drive the accumulation and distribution of capital? Questions about the long-term evolution of inequality, the concentration of wealth, and the prospects for economic growth lie at the heart of political economy. But satisfactory answers have been hard to find for lack of adequate data and clear guiding theories. In Capital in the Twenty-First Century, Thomas Piketty analyzes a unique collection of data from twenty countries, ranging as far back as the eighteenth century, to uncover key economic and social patterns. His findings will transform debate and set the agenda for the next generation of thought about wealth and inequality.
Income and output -- Growth : illusions and realities -- The metamorphoses of capital -- From old Europe to the new world -- The long-run capital/income ratio -- Capital's share vs. labor's share in the twenty-first century -- Inequality and concentration : an initial orientation -- The two worlds -- Inequality in the income from labor -- Inequality in the ownership of capital -- Merit and inheritance in the long run -- Global inequality of wealth in the twenty-first century -- A social state for the twenty-first century -- Rethinking the progressive income tax -- A global tax on capital -- The question of the public debt.
Translated from French: ( Capital au XXle siecle. English ).​
Keywords: Financial economics; CAPITAL; INCOME DISTRIBUTION; LABOUR ECONOMICS